A pilot study of the determination of organophosphate flame retardants in indoor air - Hoang, Minh Tue Thi; Duong, Hanh Thi; Le, Giang Truong; Trinh, Ha Thu (Vietnam Journal of Science and Technology, 2020)
In recent years, the production and use of organophosphate flame retardants (OPFRs) have been increased significantly due to their excellent fire resistance and the prohibition of the use of several brominated ﬂame retardants. However, there is little knowledge of levels of OPFRs in the environment, including the indoor environment, especially in Viet Nam. Therefore, the aim of this study is to investigate the occurrence and distribution of 15 OPFRs in indoor air samples collected from 3 districts of Ha Noi city, Viet Nam. Nine out of fifteen OPFRs were detected in the indoor air with the mean concentration of total OPFRs (SOPFRs) of 151 ng/m3 (ranged from 39.3 to 372 ng/m3). Congener profiles of OPFRs in dust indoor air samples showed that tris(1-chloro-2-propyl) phosphate (TCPP) was the most predominant compound in all indoor air samples with a mean concentration of 114 ng/m3 (ranged from 21.1 to 329 ng/m3), accounting for 67.5 % (ranged 43.1 - 93.0 %) of the total OPFR levels. The following is tris(2-butoxyethyl) phosphate (TBEP), which was also detected in all samples with a mean concentration of 29.4 ng/m3, accounting for 23.9% of the total OPFRs. Whereas triphenyl phospate (TPP), tris(1,3-dichloroisopropyl) phosphate (TDCPP), tributyl phosphate (TBP), and tri(2-chloroethyl) phosphate (TCEP) were found in some samples with lower concentrations (average value of 2.58; 2.48; 1.36 and 0.50 ng/m3, respectively). Concentrations of SOPFRs in the environmental apartments (ranged 166.4 - 372.0 ng/m3) were higher than those in the individual houses (ranged 39.3 - 134 ng/m3), probably attributed to strict requirements for the use of flame-retardant building materials and interior decorations of apartment buildings.